(untitled) (Bangladesh Medical Journal, 2014)
Muscle hydatidosis is rare, accounting only for 35% of all cases. We present an unusual case of a primary hydatid cyst found in the soleus muscle of a 42-year-old woman, presenting as an enlarging soft-tissue mass for 6 months associated with pain. The hydatid cyst was confined into muscle, without affecting the bone. En block surgical excision of the cyst was undertaken. Histopathologic findings confirmed the diagnosis. No recurrence occurred during the follow-up period of 8 months. Skeletal muscle echinococcosis should be considered in the differential diagnosis of limb masses, especially in endemic countries. A meticulous history taking and MR imaging is essential, while pericystectomy is an effective method of treatment. DOI: http://dx.doi.org/10.3329/bmj.v42i2.18988 Bangladesh Med J. 2013 May; 42 (2): 60-62